PENGARUH PEMANFAATAN E-LEARNING, LINGKUNGAN TEMAN SEBAYA, DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR - Anas Pratama, Haikal Firmansah; Arief, Sandy (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2019)
This study aims to examine the influence of the use of e-learning, peer group and learning motivation towards learning outcomes of Accounting in class X Accounting of SMK Hidayah Semarang. The sample of this study was students of class X Accounting SMK Hidayah Semarang with total of 41 students. A self-administered questionnaires and multiple regression analysis were used to test the research question. In addition, the results showed that there is a positive and significant effect both simultaneously and partially from the use of e-learning, peer group and learning motivation towards learning outcomes in class X Accounting at SMK Hidayah Semarang. The improvement and intensity in using e-learning strategies, teacher's attention to the studentsâ€™ peer environment specifically on cooperation and competition among students, and students' intelligence in interacting and establishing fair cooperation in the academic context with their peers are very important factors towards learning outcomesÂ Keywords: learning outcomes; e-learning; peer group; motivation